Parental Awareness about Thumbsucking: The Earliest Addiction of Children - Sudipta Sahu1, Debasruti Naik2, Kajal Kiran Sahu3, Nikita Sahu4, Sharmistha Mohanty5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Thumb sucking is a type of non-nutritive sucking that occurs in the early daysof the 29th week of gestation.Parents should be concerned about the health of their kids. Parents have to look after their children goodhealth who should raisedevoid of developing any behavior that would endanger their suitable development.Thumb sucking is one of the concerned habitsthat makes every parents worry about as their babies growand grow to be toddlers. Parents keep speculating if the habit will continue, or if they have to look for helpto stop it. This review article discusses all the importance of habits related to the oral health of a child andfocus on the need of awareness among parents about thumbsucking.